Redefining and “Re-presenting” Native American Collections and Curatorial Practice - Kopelva, Shannon R (My University, 2017)
The purpose of this study was to describe the collections and curatorial practices of three O’odham museums and centers in Arizona. Specifically, this study explored how these museums amended the frameworks of preservation, accessibility to collections, and stewardship to suit their needs and how traditional care methods were incorporated. Since the tribal museum movement of the 1960s and 1970s, tribal museums and cultural centers have adopted Western collections management and curatorial museum practices and policies, often operating under pre-established museum models that contrasted against world and cultural views of Native people. Although much can be learned from Western collections and curatorial practice and policy, Native American worldviews and beliefs presented an alternative to the approach of Western practice and policy. Data was collected through semi-structured, one-on-one interviews conducted with museum staff at O’odham tribal museums. Study results suggested that tribal museum practitioners employed best practices that incorporated both Western frameworks and Native American cultural values, sought to foster connection to their home communities and provided spaces that maintained tribal culture and history. A primary limitation was the small sample of tribal museums studied and findings may not be transferrable to phenomena taking place at tribal museums across the country.
Thesis (Master's)--University of Washington, 2017-06
Keywords: Collections Management; Curatorial; Native American; Traditional Care; Museum studies; Museology